(untitled) (KULT_online, 2018)
The edited volume Rancière and Law by Mónica López Lerma and Julen Etxabe collects a set of approaches to thinking about law and legal problems via the work of Jacques Rancière. Rather than bringing together his explicit statements on law, they try to transfer his way(s) of thinking to the field of legal theory. Here special attention is drawn to Rancière’s differentiation of “police”, as a certain fixed order, and “politics”, as acts disrupting this order. Without placing law on one of these sides exclusively, instead its ambiguous state between these opposing strands is delineated in various attempts, ranging from case studies in the history of ideas to the field of aesthetics. Thus, the volume sheds an original light on legal problems and inner conflicts developed through a Rancièrean lens.